Pelaksanaan Inventarisasi Kekayaan Intelektual Komunal Sebagai Upaya Melindungi Warisan Budaya Di Kalimantan Timur - yatini yatini (Yuriska: Jurnal Ilmiah Hukum, 2021)
Background: Communal Intellectual Property (KIK) as a wealth of Indonesian cultural heritage must be protected, preserved, developed, and/or utilized through an inventory, which will then be collected into the KIK Data Center in Indonesia. For the regions with KIK protection is not only a form of legal protection but also aims to encourage the economy of the community in an area and as an effort to protect cultural heritage as the identity of a region. The purpose of this study was to identify the potential and constraints in the KIK inventory in East Kalimantan Province and explore the efforts of the East Kalimantan local government in implementing the KIK inventory. Research Methods: The type of research used was socio-legal with a statutory approach and a social approach to get the maximum form of inventory implementation. The technique of data analysis was carried out, namely by analyzing statutory regulations that had been inventoried to obtain legal certainty for the implementation of the KIK inventory. Furthermore, analyzing factual data in the implementation of KIK protection and problems in the community, and offering strategic steps in organizing KIK inventory in providing legal protection for KIK in East Kalimantan. Findings: The findings after the discussion were, first, the identification of the KIK potential in East Kalimantan was carried out with an inventory. The inventory of KIK in East Kalimantan as an effort to protect the law of cultural works was carried out on a defensive basis. Second, implementation of KIK potential inventory in East Kalimantan are in two forms, namely, an inventory carried out by the Ministry of Law and Human Rights through the KIK registration mechanism, then entered into the KIK Data Center, and Education and Culture Office through a recording mechanism which was then determined become WBTB. Then, there were still differences in perceptions within the internal government and the lack of public understanding regarding the substance of the KIK inventory, which is the main obstacle in implementing the inventory. Conclusion: Conclusion from the discussion, namely, first, the inventory of potential KIK is still experiencing problems and has an impact on the non-optimal legal protection of cultural works in East Kalimantan. Second, various efforts have been made by the Ministry of Law and Human Rights, the Department of Education and Culture, and the community, but have not been able to synergize the entire system in implementing the inventory. As a recommendation regarding this matter, the first is to share perceptions and synergize between the Ministry of Law and Human Rights and the Education and Culture Office. Second, the inventory system must accommodate all social facts, objective realities, and consider local cultural values. Besides, special treatment is needed for the community by maximizing socialization, education, and assisting in the KIK inventory.